Increased capsaicin receptor TRPV1-expressing sensory fibres in irritable bowel syndrome and their correlation with abdominal pain. Issue 7 (5th February 2008) - Akbar, A; Yiangou, Y; Facer, P; Walters, J R F; Anand, P; Ghosh, S
Abstract : Objective: The capsaicin receptor TRPV1 (transient receptor potential vanilloid type-1) may play an important role in visceral pain and hypersensitivity states. In irritable bowel syndrome (IBS), abdominal pain is a common and distressing symptom where the pathophysiology is still not clearly defined. TRPV1-immunoreactive nerve fibres were investigated in colonic biopsies from patients with IBS, and this was related to abdominal pain. Methods: Rectosigmoid biopsies were collected from 23 IBS patients fulfilling Rome II criteria, and from 22 controls. Abdominal pain scores were recorded using a validated questionnaire. TRPV1-, substance P- and neuronal marker protein gene product (PGP) 9.5-expressing nerve fibres, mast cells (c-kit) and lymphocytes (CD3 and CD4) were quantified, following immunohistochemistry with specific antibodies. The biopsy findings were related to the abdominal pain scores. Results: A significant 3.5-fold increase in median numbers of TRPV1-immunoreactive fibres was found in biopsies from IBS patients compared with controls (p<0.0001). Substance P-immunoreactive fibres (p = 0.01), total nerve fibres (PGP9.5) (p = 0.002), mast cells (c-kit) (p = 0.02) and lymphocytes (CD3) (p = 0.03) were also significantly increased in the IBS group. In multivariate regression analysis, only TRPV1-immuno-reactive fibres (p = 0.005) and mast cells (p = 0.008) were significantly related to the abdominal pain score. Conclusions: Increased TRPV1 nerve fibres are observed in IBS, together with a low-grade inflammatory response. The increased TRPV1 nerve fibres may contribute to visceral hypersensitivity and pain in IBS, and provide a novel therapeutic target.